STORAGE DESIGN OF HARVESTED DRY GRAIN AND RICE WITH PASSIVE ENERGY BUILDING: Abstract - Sumarjo, Jojo Sumarjo; siswadi, siswadi (Barometer, 2024)
Passive design is a way to save energy through the passive use of solar energy, that is, without converting solar energy into electrical energy. the passive design relies more on the ability of engineers how the design of the building itself can "anticipate" external climate problems. In Indonesia as a tropical region, cooling systems and lighting systems are the largest contributors to building energy consumption, accounting for 24.7% and 16% respectively of the total building energy consumption. The purpose of this research is to do storage modeling using the passive energy method. The procedure is carried out with a combination of energy calculations around storage and CAD. CAD software is used to create 3D solid surface drawings and shapes. Then draw several options for the air openings that will be used. The results showed that based on the month of observation, the value of heat energy that occurred in the storage of dry harvested grain and rice with passive energy buildings was lower and heat energy was higher in June. Therefore, the solution for choosing the type of opening in January is required an opening percentage of 25% and for June, an opening with a percentage of 50% is required).